2020
DOI: 10.18632/oncotarget.27307
|View full text |Cite
|
Sign up to set email alerts
|

Identification of signature genes associated with therapeutic resistance to anti-VEGF therapy

Abstract: VEGF-mediated tumor angiogenesis is a validated clinical target in many cancers, but modest efficacy and rapid development of resistance are major challenges of VEGF-targeted therapies. To establish a molecular signature of this resistance in ovarian cancer, we developed preclinical tumor models of adaptive resistance to chronic anti-VEGF treatment. We performed RNA-seq analysis and reverse-phase protein array to compare changes in gene and protein expressions in stroma and cancer cells from resistant and resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 47 publications
1
6
0
Order By: Relevance
“…For instance, TSGA10 (testis specific Gene Antigen 10), which acts as a tumor suppressor in many types of human cancers [ 60 ] and inhibits VEGF -induced angiogenesis [ 61 ] was not differentially expressed in anti- VEGF resistant condition. Further, recent RNA seq analysis of anti- VEGF resistant ovarian cancer model showed upregulation of apelin/ APJ receptor signaling pathway [ 62 ]. However, this receptor-ligand pair gene expression was not altered in anti- VEGF resistant glioma described in the present study, probably suggesting that mechanisms underlying anti VEGF resistance are different in different tumors.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, TSGA10 (testis specific Gene Antigen 10), which acts as a tumor suppressor in many types of human cancers [ 60 ] and inhibits VEGF -induced angiogenesis [ 61 ] was not differentially expressed in anti- VEGF resistant condition. Further, recent RNA seq analysis of anti- VEGF resistant ovarian cancer model showed upregulation of apelin/ APJ receptor signaling pathway [ 62 ]. However, this receptor-ligand pair gene expression was not altered in anti- VEGF resistant glioma described in the present study, probably suggesting that mechanisms underlying anti VEGF resistance are different in different tumors.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study showed that apelin inhibition could prevent resistance and metastasis associated with anti-angiogenic therapy. 23 , 24 Apelin was associated with the promotion of hepatocellular carcinoma through activating PI3K/Akt pathway and was a druggable target. 25 In addition, apelin can induce the lymphangiogenesis and, accordingly, play an important role in lymphatic tumor progression.…”
Section: Discussionmentioning
confidence: 99%
“…Hypoxia is the main driving force to initiate angiogenesis and promote tumor growth and metastasis. If the angiogenesis in the tumor is inhibited, the tumor can be effectively treated (Aktan & Ozmen, 2019; Haas et al, 2021; Jaiprasart et al, 2020; Kälin et al, 2007). The current existing antiangiogenesis therapy can cause various side effects, such as local hypoxia and tumor metastasis.…”
Section: Role Of Apelin/apj System In Cancer Development and Progressionmentioning
confidence: 99%
“…Apelin/APJ system can significantly reduce the therapeutic effect of VEGF inhibitors in patients with ovarian cancer. The efficacy of bevacizumab in patients with ovarian cancer can also be oppressed by apelin, resulting in a significant decrease in the disease‐free survival rate of patients and affecting their prognosis (Frontiers Editorial Office, 2021; Jaiprasart et al, 2020). In the lymph node tissues of patients with Stage III and IV ovarian cancer, the relevant immune response of apelin and APJ was detected, indicating that the apelin/APJ system plays a crucial role in the metastasis and prognosis of serous ovarian cancer (Köbel et al, 2008; Unal et al, 2020).…”
Section: Role Of Apelin/apj System In Cancer Development and Progressionmentioning
confidence: 99%